Systematic Risk of Malaysian Stock / Tay Bee Hoong, Tan Yan Ling, Nur'Asyiqin Ramdhan and Zulkifli Mohamed - Tay, Bee Hoong; Tan, Yan Ling; Ramdhan, Nur'Asyiqin; Mohamed, Zulkifli (2012)
The aims of this study are to examine the stability and predictive ability of beta values as a forecasting tool to evaluate the investment risk. Beta values are computed based on Single Index Model proposed by Sharpe (1964). Stability of beta is examined based on a simple paired observation test while predictive ability of betas is investigated based on correlation analysis for the one hundred stocks listed in Bursa Malaysia from the year 1998 to 2007. The study reveals that even though the beta values are not stable during the observation period for Malaysian stocks, however, it can be predicted with confidence from those in an earlier period. The results suggest that the investors need to be careful when examine the stability of beta values for the stocks as there may be changing economic conditions which can contribute to the changing of the company profile over time. Nevertheless, investors and fund managers may still use beta as one of their risk forecasting tools as beta can be predicted with certain degree of accuracy from those in an earlier period.